Antimicrobial Property of Extracts of Indian Lichen against Human Pathogenic Bacteria - Srivastava, Priya; Upreti, D. K.; Dhole, T. N.; Srivastava, Apurva K.; Nayak, Meghanand T. (Interdisciplinary Perspectives on Infectious Diseases, 2013)
Context. Usnea ghattensis G. Awasthi (Usneaceae) endemic fruticose lichen found growing luxuriantly in Northern Western Ghats of India, it also contains Usnic acid as a major chemical and tested against some human pathogenic bacteria. Objective. To explore antimicrobial properties of Usnea ghattensis against some human pathogenic bacteria. Materials and Methods. The lichen was extracted in acetone, methanol, and ethanol. In vitro antimicrobial activity was tested initially by Kirby-Bauer technique of disc diffusion method and was confirmed by minimum inhibitory concentration using Broth microdilution method according to the NCCLS guidelines. Results. Ethanol extract was most effective against Bacillus cereus and Pseudomonas aeruginosa with a zone of inhibition 29.8 ± 0.6 mm and 12.3 ± 0.5 mm diameters at a concentration of 0.2 mg/mL. Acetone and methanol extract demonstrated almost similar activity against Staphylococcus aureus and the zone of inhibition was 24.6 ± 0.5 and 24.7 ± 0.4 mm. Only methanol extract was showing activity against Streptococcus faecalis with a 13.5 ± 0.8 mm zone. MIC value noted against Staphylococcus aureus and Streptococcus faecalis was 6.25 μg/mL and 25 μg/mL, whereas against Bacillus cereus and Pseudomonas aeruginosa, MIC calculated was 3.125 μg/mL and 200 μg/mL, respectively. Conclusion. The present study demonstrates the relatively higher activity of this lichen against not only gram (+) but significantly also against gram (−) bacteria. This indicates that this lichen might be a rich source of effective antimicrobial agents.